Penguatan Moderasi Beragama dan Sikap Demokrasi pada Santri Pondok Pesantren Edi Mancoro Desa Gedangan Kecamatan Tuntang Kabupaten Semarang - Nurlaila Syahri Syarifah; Guntur Cahyono (Arfannur, 2022)
This study discusses the Strengthening of Religious Moderation and Attitudes of Democracy in Santri Pondok Pesantren Edi Mancoro. The purpose of this research is to find out (1) how description for religious moderation and democratic attitude? (2) how to strengthen religious moderation and democratic attitudes to students at the Edi Mancoro Islamic Boarding School? (3) what are the obstacles and support for strengthening religious moderation and democratic attitudes to students at the Edi Mancoro Islamic Boarding School? This study uses field research using a qualitative descriptive approach. Data collection is done by observation, interviews and documentation. Meanwhile, data analysis used three activities, namely data reduction, data presentation and conclusion drawing. The results showed that religious moderation is the attitude of wasath (middle) in religion. The attitude of democracy is a response attitude in implementing democracy in life, how to respect and respect different opinions in a deliberation. Strengthening religious moderation and democratic attitudes in the students of the Edi Mancoro Islamic boarding school with activities inside the boarding school, namely interfaith discussions, multicultural seminars, seloso kliwon, internal students and the election of the head of the boarding school. The existing obstacle is that the students are still passive in activities at the pesantren. Technological developments that can affect students who cannot filter information. Then for the strengthening support, the majority of the students are students who have an open mind in addressing the existing problems. ABSTRAKPenelitian ini membahas tentang Penguatan Moderasi Beragama dan Sikap Demokrasi di Pondok Pesantren Santri Edi Mancoro. Tujuan penelitian ini adalah untuk mengetahui (1) bagaimana gambaran moderasi beragama dan sikap demokratis? (2) bagaimana penguatan sikap moderat beragama dan demokratis pada santri di Pondok Pesantren Edi Mancoro? (3) apa saja kendala dan dukungan penguatan moderasi beragama dan sikap demokratis pada santri di Pondok Pesantren Edi Mancoro? Penelitian ini menggunakan penelitian lapangan dengan menggunakan pendekatan deskriptif kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Sedangkan analisis data menggunakan tiga kegiatan yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa moderasi beragama merupakan sikap wasath (tengah) dalam beragama. Sikap demokrasi merupakan sikap respon dalam melaksanakan demokrasi dalam kehidupan, bagaimana cara menghormati dan menghargai perbedaan pendapat dalam suatu musyawarah. Penguatan moderasi beragama dan sikap demokratis pada santri pondok pesantren Edi Mancoro dengan kegiatan di lingkungan pesantren yaitu diskusi lintas agama, seminar multikultural, seloso kliwon, internal santri dan pemilihan ketua pondok. Kendala yang ada adalah santri masih pasif dalam beraktivitas di pesantren. Perkembangan teknologi yang dapat mempengaruhi siswa yang tidak dapat menyaring informasi. Kemudian untuk dukungan penguatan, mayoritas mahasiswa adalah mahasiswa yang berpikiran terbuka dalam menyikapi permasalahan yang ada. Kata Kunci: Moderasi Beragama; Sikap; Demokrasi